Industry 4.0 and its Impact on Quality Management: A Systematic Literature Review from 2021-2024 - Osorio-Paredes, Liney; Rivas Mendoza, Milagros Isabel; Vilcherres Castillo, Geraldine Steffani; Morales Marcelo, Dana Muriel; Estrada Espinoza, Johan Alexander (LACCEI, 2024)
This systematic research aims to analyze the impact of using 4.0 technologies on quality management, as well as the tools of Industry 4.0 technologies in improving quality management. For this purpose, a systematic review of the scientific literature published between 2021 and 2024 in the Scopus database was conducted, identifying 20 relevant studies that met the determined eligibility criteria. The results show a positive impact between 4.0 technologies and quality management, with the potential to reduce the use of unnecessary energy and resources through the transmission of reports and the analysis of production operations using various technological trends studied in the reviewed articles. The proposed use of IT management tools includes the Internet of Things, Big Data, digital twins, blockchain, modal analysis, Failure Modes and Effects Analysis (FMEA), and smart factories. Additionally, some bibliometric indicators are presented: the journal where most articles on the subject are published is Sustainability, the year with the highest publication rate was 2022, and the author Wolniak with two publications. In conclusion, this study highlights the importance of implementing 4.0 technologies to achieve successful quality management with a more sustainable and responsible approach to the entire process management.